Bentuk Penyajian Tari Sukat Pada Mata Kuliah Koreografi di Universitas PGRI Palembang - Dekriyansah, Dekriyansah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to describe the form of presentation of the Sukat dance in the choreography exam at Universitas PGRI Palembang which was inspired by a regional song from Musi Banyuasin regency. This dance work was created to fulfil the failure assignment of the choreography course, the Sukat dance is sourced from a regional song from Musi Banyuasin regency entailed mare-mare which tells the story of a girl who wants to go abroad. This study uses a qualitative method, the data collection process includes several techniques used, namely, observation techniques, documentation, and interviews. The purpose of this study is to realize a presentation of a new dance style without changing the essence of the source. The result of this dance presentation research is to get creativity by providing variations in aspects of movement, floor patterns, costumes, make up, and in arranging the stage atmosphere. So that the realization of the gambles Sukat which still maintains the essence of its source.